O44 Comparing the Relationship Between Food Parenting Practices and Concern for Child Weight Between Siblings - Vollmer, Rachel L. (Journal of nutrition education and behavior, 2021)
Parental concern for child weight can impact food parenting practices utilized; however, most studies only ask parents about 1 child in the family. The objective of this study was to compare the difference in food parenting practices based upon parent concern and/or perception of child weight among siblings. This quantitative, cross-sectional study recruited U.S. parents (n = 63) who had more than 1 child between the ages of 2.5 (M = 4.12, SD = 1.57) and 10 (M = 7.52, SD = 1.97) years old to complete an online survey. Parents were mostly White (75%), non-Hispanic (76%) females (79%). Each parent completed the Comprehensive Food Parenting Questionnaire, child weight concern and perception items from the Child Feeding Questionnaire for their oldest and youngest child (2.5-10 years old). Parents also reported demographic information. Linear regression was utilized to compare the relationships between parent concern and perception of child weight (independent variable) and food parenting practices (dependent variable) for the oldest and youngest child. Child age and gender were used as control variables. There were differences in the relationships between food parenting practices and weight concern/perception for younger and older children. For example, for the older child only, parents used more pressure to eat if they were less concerned about their child's weight (β = −0.32, SE = 0.15, P = 0.034). Additionally, if parents were highly concerned about their child's weight, they reported more use of restriction for weight control, but this relationship was stronger for the older child (β = 0.55, SE = 0.11, P < 0.001) compared to the younger child (β = 0.34, SE = 0.16, P = 0.039). Parents may use different food parenting practices for children based upon their perception or concern for their child's weight, which may be counterproductive. Concerned parents may be especially important targets for food parenting interventions.